Self-organization for everyday peacebuilding: The Guardia Indígena from Northern Cauca, Colombia. (February 2020) - Chaves, Paola; Aarts, Noelle; van Bommel, Severine
The Nasa indigenous group's Guardia Indígena, whose primary goal is to protect indigenous people and their territories from all types of armed groups, is a nonviolent self-protection organization in Northern Cauca, Colombia. On 5 November 2014, while peace talks were ongoing between the Revolutionary Armed Forces of Colombia (FARC) and the Colombian government, two Guardia Indígena members were shot dead by FARC guerrillas. Without guns or physical violence, indigenous guards captured seven guerrillas responsible for the crime, and, four days later, indigenous organizations held a trial and sentenced the rebels to imprisonment. This article describes those events and investigates how the unarmed guards managed to capture the guerrillas and bring them to trial. The self-organization concept is used to gain insights into the mechanisms and strategies deployed. The mechanisms of the Guardia Indígena include constructing and applying specific social norms and values, developing a common goal, and applying a flexible mix of centralized and decentralized ways of organizing. By combining and activating these mechanisms at carefully chosen moments, indigenous people have succeeded in organizing themselves as a collective movement that is powerful enough to confront armed groups without using violence.